Pengaruh Job Demands Terhadap Workplace Well-Being Pada Karyawan Hotel The ZHM Premiere Padang (International Forum of Researchers and Lecturers, 2024)
This research was conducted to determine the effect of job demands on workplace well-being. This study is quantitative research. The ZHM Premiere Hotel Padang's staff members made up the study's population. There were 104 respondents in the study's sample. Data for this study was gathered by distributed questionnaires. Then the data analysis by regression analysis using the classic assumption test, namely the normality test, linearity test, and heteroscedasticity test which is processed using the SPSS version 29 program. The data analysis result show that job demands have a negative and significant effect on workplace well-being. being with a standardized coefficient value of -0.965 with t count (-37.368) with a significance of 0.001 < 0.05. This shows that every increase in job demands units will provide -1,230 units of workplace well-being.